Interactive effects of irrigation and nitrogen management on greenhouse gas emissions and resource efficiency in alfalfa production - Qu, Tianyi; Li, Jiabei; Song, Xiaodan; Luan, Xiaobo; Pang, Jie; Sun, Shikun; Wang, Yubao (Frontiers in Plant Science, 2026)
IntroductionMitigating agricultural greenhouse gas (GHG) emissions while maintaining forage productivity is a key challenge under global carbon-neutrality goals. To evaluate the environmental and agronomic trade-offs of irrigation and nitrogen management, a field experiment was conducted in an arid region of Northwest China.MethodsTwelve irrigation-nitrogen treatment combinations were applied to alfalfa (Medicago sativa L.) to quantify N2O, CO2, and CH4 fluxes, global warming potential (GWP), and resource-use efficiencies.ResultsResults showed that soil water-filled pore space and available nitrogen strongly regulated N2O, emissions, with peaks occurring within one week after irrigation or fertilization. Excessive water and nitrogen inputs significantly increased GHG emissions and reduced irrigation water productivity (IWP) and partial factor productivity of nitrogen (PFPN).Discussion and ConclusionConversely, the high-water, moderate-nitrogen regime (300 mm irrigation + 120 kg N ha-1) achieved a balanced outcome—sustaining high yield while reducing cumulative N2O emissions by 29.5-93%, total GWP (LCA-based) by 24.1%, and greenhouse gas emission intensity (GHGI) by 29.0% relative to conventional high-input management (W2N3). These preliminary findings suggest a water-nitrogen synergy zone that improves yield-GHG trade-offs, though multi-year validation is required.